The 30-minute gardener : cultivate beauty and joy by gardening every day - Loades, Greg (Timber Press, 2023)
"There are lots of aspiring gardeners out there. But a large number of them-especially younger ones, with demanding jobs, growing families, and limited space-either don't have the time to garden traditionally, or are scared off from the very notion and have no idea where to start. Greg Loades comes to the rescue in this detailed, inspiring book. He shows the reader how much can actually be accomplished in no more than 30 minutes a day, from simple tasks such as renovating a rose bush or planting a layered bulb display to more complex ones like laying a patio or building a green roof. By laying out the details of the projects-which include both in-the-ground ornamental and vegetable gardening as well as container projects-he shows the reader exactly how to create a welcoming, rewarding haven that will quickly become an indispensable part of their family's lifestyle"--